Pengaruh Strategi Pembelajaran Role Playing Terhadap Keaktifan Belajar PAI Siswa Kelas VIII di SMPN 1 Batang Kapas - Safna Safna; Hamdi Abdul Karim (Moral : Jurnal kajian Pendidikan Islam, 2025)
This study was motivated by the discovery that some students of SMPN 1 Batang Kapas, especially students of class VIII, were less active in participating in PAI learning when teachers or tutors provided learning materials because the teacher focused on only one strategy, which caused students to get bored about learning easily. In this, a good strategy is needed to overcome this problem, and the strategy that is considered capable of overcoming this problem is the role-playing strategy. Thus, this study aims to determine the effect of role-playing strategies on the active learning of PAI for students of class VIII of SMPN 1 Batang Kapas. The research used in this study is experimental research with a quantitative approach. The population in this study consisted of all students of class VIII of SMPN 1 Batang Kapas, consisting of 4 classes with a total of 116 students. The sample in this study used a cluster random sampling technique and two classes were obtained as samples, with class VIII.I as the control class and class VIII.II as the experimental class. Data were collected through a questionnaire and analyzed using the independent sample t-test. Based on the results of the conducted research, the results show that the role-playing strategy has an effect on students' active learning, which is proven by the results of the independent sample t-test, namely at a sig-value of 0.002. < 0.05 and a calculated t-value > t-table, namely 3.213 > 2.00